RANCANG ULANG USER INTERFACE DAN USER EXPERIENCE PADA STARS USKSW MENGGUNAKAN METODE USER CENTERED DESIGN DAN HEURISTIC EVALUATION - Immanuel Gratia Wibawa Herbert Sihombing; Nina Setiyawati (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
STARS UKSW is a web-based system used to formally record student activities at Satya Wacana Christian University. To ensure that this website can be used effectively, it is important to pay attention to the quality of the user interface (UI). In order to evaluate the extent to which the interface of this website is optimal, a usability test was carried out using the heuristic evaluation method developed by Jacob Nielsen. The results of this study show that students feel confused when using the website, especially because of the unfamiliar layout and icons, as well as difficulties in understanding the flow of using the system. A redesign to improve the user experience (UX) was undertaken based on these issues. The User-Centered Design (UCD) approach is applied in this redesign process to ensure that the resulting design is more aligned with the needs and choices of the users. This is expected to improve the overall quality of the STARS UKSW website by creating a more effective design in line with the target users. .